2005
DOI: 10.1002/mrc.1651
|View full text |Cite
|
Sign up to set email alerts
|

1H NMR assignment and secondary structure of recombinant RGD‐hirudin

Abstract: The conformation of a new recombinant RGD-hirudin, which has the activities of anti-thrombin and anti-platelet aggregation, was investigated by multi-dimensional NMR spectroscopy. The 1H NMR spectra of this protein are assigned in a sequential manner by using a combination of 2D NMR techniques to demonstrate through-bond and through-space (<5 A) connectivities. The secondary structure of recombinant RGD-hirudin was deduced from chemical shift indices, sequential NOEs and 3J(HNalpha) coupling constants. The res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 23 publications
(19 reference statements)
0
10
0
Order By: Relevance
“…Incorporation of an RGD motif by replacement of Ser 32 ‐Asp 33 ‐Gly 34 with the tripeptide Arg‐Gly‐Asp between cysteine residues 5 and 6 of hirudin variant HV1 did not alter its antithrombin activity . The RGD motif acts as a recognition site for integrin binding and facilitates the inhibition of platelet aggregation by the leech factors ornatin , decorsin , and RGD–hirudin .…”
mentioning
confidence: 99%
“…Incorporation of an RGD motif by replacement of Ser 32 ‐Asp 33 ‐Gly 34 with the tripeptide Arg‐Gly‐Asp between cysteine residues 5 and 6 of hirudin variant HV1 did not alter its antithrombin activity . The RGD motif acts as a recognition site for integrin binding and facilitates the inhibition of platelet aggregation by the leech factors ornatin , decorsin , and RGD–hirudin .…”
mentioning
confidence: 99%
“…The dispersion of the signals in the 1 H dimension covers the whole spectral area. As the proton resonances in TOCSY and NOESY spectra were assigned for r-RGD-hirudin [6], the assignment of 15 N-1 H signals can be performed more easily. A 3D 1 H-15 N edited HSQC-TOCSY spectrum [27] was acquired to correlate the 15 N with C H and side-chain protons.…”
Section: Nmr Spectroscopymentioning
confidence: 99%
“…Continuous structure studies have focused on the structure-function relationship of r-RGD-hirudin. The solution structure of r-RGD-hirudin was determined by 1 H NMR spectroscopy; on the basis of this structure, Song et al suggested a mechanism for r-RGDhirudin/thrombin binding and suggested that the r-RGD hi- [6,7]. The precise mechanisms and sites of interaction between r-RGD-hirudin and its receptors remain unknown.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Previous structural information from X-ray studies had revealed at least 13 sites near the cognate substrate-recognition site where hirudin might form short proton bridges. To aid locating the sites of possible short proton bridges between thrombin and hirudin, we employed several analogs of hirudin: hirunorm IV and hirunorm V [ 48 , 53 , 54 ], r-RGD-hirudin (recombinant 32SGD34 type 2 hirudin) [ 51 ] and an Nα(Me)Arg-peptide [ 52 ]. The hirunorms have three amino acids of the N-terminal sequence of hirudin followed by a linker and 10 amino acids of the C-terminus of hirudin, but are about hundred times less effective inhibitors of α-thrombin than the parent compound.…”
Section: Introductionmentioning
confidence: 99%